(untitled) (مجلة إحالات, 2026)
This study begins by observing the extreme discrepancy in the translation of Western scientific terms in Arabic studies in general, and in semiotic studies in particular. This indicates the existence of a problem in the translation of semiotic terminology in Arabic literature. We have encountered incomplete translations lacking a cognitive identity, in addition to the multiplicity of these translations, which often clash. We find a vast number of translations for a single term: (For example, see the numerous translations of the term "Sémiotique"). This disturbs the mind of the semiotic researcher and exhausts his energies to no avail. It is imperative that he consult the original Western source and then compare it with the Arabic translation in order to understand its cognitive content.